2010
DOI: 10.1063/1.3484043
|View full text |Cite
|
Sign up to set email alerts
|

Inversion layer carrier concentration and mobility in 4H–SiC metal-oxide-semiconductor field-effect transistors

Abstract: Free electron concentration and carrier mobility measurements on 4H–SiC metal-oxide-semiconductor inversion layers are reported in this article. The key finding is that in state-of-the-art nitrided gate oxides, loss of carriers by trapping no longer plays a significant role in the current degradation under heavy inversion conditions. Rather, it is the low carrier mobility (maximum∼60 cm2 V−1 s−1) that limits the channel current. The measured free carrier concentration is modeled using the charge-sheet model an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
71
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 110 publications
(75 citation statements)
references
References 32 publications
4
71
0
Order By: Relevance
“…Coulomb scattering had often been proposed as the main limiting factor, but it turned out that thermally activated transport or electron localization in inversion layers [27] are more likely to be responsible, because of very high density of interface states near the conduction band edge [28], [29]. The interface-state density in SiC (0001) MOS structures was so high before process optimization of interface nitridation that the integrated density of interface states was of the same order as the induced sheet electron density (electron trapping effect) [30], [31]. The D it values near the conduction band edge for 4H-SiC (0001) MOS was remarkably reduced by optimization of the nitridation process, as far as the D it was deduced by the conventional high-low method.…”
Section: Discussionmentioning
confidence: 97%
“…Coulomb scattering had often been proposed as the main limiting factor, but it turned out that thermally activated transport or electron localization in inversion layers [27] are more likely to be responsible, because of very high density of interface states near the conduction band edge [28], [29]. The interface-state density in SiC (0001) MOS structures was so high before process optimization of interface nitridation that the integrated density of interface states was of the same order as the induced sheet electron density (electron trapping effect) [30], [31]. The D it values near the conduction band edge for 4H-SiC (0001) MOS was remarkably reduced by optimization of the nitridation process, as far as the D it was deduced by the conventional high-low method.…”
Section: Discussionmentioning
confidence: 97%
“…This evaluation can be performed based on Hall effect measurements and has already been reported in the literatures. [20][21][22] These reports show that the free carrier density increases linearly with gate voltage with a slope close to C OX /e, which indicates that D IT above E C 017109-9…”
Section: Discussionmentioning
confidence: 99%
“…However, to discuss accurately the effects on l FE , the total D IT including the interface states that trap electrons at high gate voltage (or electric field) is necessary. Other techniques such as Halleffect measurements [23][24][25] or thermally-stimulated-current measurements 26,27 are necessary to evaluate the interface states at high gate voltage (or electric field). Okamoto et al showed the effect of trapped electrons that increase with oxide electric field on the field-effect mobility.…”
mentioning
confidence: 99%